DATA COMMUNICATION AND COMPUTER NETWORK EASY TO LEARN AND SIMPLE TO DEVELOP - Vani, M.P (Nition Press, 2019)
Data Communication and Computer Network: Easy to Learn and Simple to Develop is ideal for self-study, as it covers all essential topics in depth and is easy to understand. The author's unique approach thoroughly illustrates the theoretical and practical aspects of data communication and the computer network, and the technologies and the tools that academic and network managers simply must know. This textbook is perfect for students pursuing their B.E., B.Tech., M.C.A., B.Sc. (Computer Science), or BCA degrees. It presupposes no prior experience with data communication and computer network on the part of the reader and serves as a comprehensive introduction to data communication and computer network concepts and network application development. Data Communication, Data Representation Layered Tasks, TCP/IP Protocol Suite, Physical Layer and Media, Transmission Impairment, Multiplexing, Data Link Layer, UDP and Application Layer are some of the concepts that the book deals with.